Towards a comprehensive internationalization of the curriculum: challenges and opportunities for Colombia - Olaya Mesa, Marian Lissett (Praxis, 2024)
Resumen This paper constitutes an analysis of the internationalization activities that higher education institutions at a national and international level are considering to enhance internationalization of the curriculum. A literature review was conducted in 50 published research articles between 2014 and 2023. The selected articles foundation was the internationalization process in higher education, specifically the internationalization at home towards a more comprehensive internationalization of the curriculum. This literature review evidences how higher education has changed and what strategies have been widely used to adapt education to current issues. In this vein, this literature exploration serves as a guide to bridge the gaps found to promote a comprehensive curriculum internationalization in public universities in Colombia. It concludes by emphasizing the importance of consolidating collaborative research and strengthening the English language as a fundamental axis in global communication.